Characterizing a Student-centered University: What do students think? - Oneil N Madden (International Journal of Education and Humanities, 2025)
Higher education institutions cannot exist without students, deemed their primary asset. This is why many tertiary institutions have begun adopting a student-consumer approach to improve student satisfaction and student-centeredness. However, the concept of student-centeredness is understudied, and there remains no unified definition of what it constitutes. This study hopes to expand on the limited existing literature. To achieve this, the research sought to understand students’ perceptions of whether their institution is student-centered. Sixty-two students from two private universities responded to an online questionnaire. Data was analyzed using qualitative content analysis. Findings reveal that student-centeredness is complex, multi-dimensional, and viewed based on students’ expectations and experiences. Nevertheless, a student-centered university encompasses a safe and welcoming learning environment that validates students’ efforts, listens to their concerns and recommendations, caters to their holistic development, and provides the requisite resources for student success. Even though both private institutions make some efforts to be student-centered, findings suggest notable weaknesses that undermine total student-consumer satisfaction, which raises the need for operational and policy review. Improvements in communication, responsiveness, and a better balance between financial goals and student well-being are needed to improve student-centeredness. The study has implications for how technology could enhance student satisfaction outcomes